UNITY IN RESTORING: A STUDY ON HEALING ATTRIBUTES OF PERSIAN GARDEN - Ramyar, Reza (Journal of Islamic Architecture, 2011)
Spending time in a Persian garden gives one the impression of being away and a sense of  connection with nature. These feelings alleviate mental fatigue, or stress and bring about mental restoration. Simply, one feels mentally refreshed after visiting and strolling in a Persian garden.  The motivation for the research is to evaluate the theory that whether Persian traditional garden can be used as a restorative garden or even its design principles can be employed to create an environment of such kind. The main areas of investigation in this paper include  understanding restorative attributes provided with the garden on visitors. Persian garden provides opportunities that intuitively engender restorative attributes which can fully be felt by being there, whether it was intended for such a purpose or not. The paper tries to imply that the aim of creation of such spaces (Persian garden) was so supreme that restoration can be  considered as one of the subjects which arouses from a dominant interrelation between human and space (nature) in a common entire inherence.   Keyword: Persian garden, restorative garden, healing attributes, mentally refresh